La temporalidad del canon y su construcción en la historia del arte a través del museo de copias en el siglo XIX - Gallipoli, Milena (Historiografías, 2020)
The nineteenth century was witness of a crucial institutionalization in the arts thanks to the foundation of museums of copies of sculptural masterpieces in plaster cast. This article examines in what manner the museum of artistic reproductions visualized, constructed and implemented the canonical account of art. We defend the hypothesis that this institution was the most suitable place to harbour a vision of history which turned out to be a mix between the idea of historia magistra vitae and the modern concept of progress. Through the history of concepts such as canon and classical we shall study the application of these categories to the realm of artistic education. Keywords History of art, museum, plaster casts, canon, classical, historical-artistic past.